Successful Management of Grade III Tetanus with Therapeutic Plasma Exchange: A Case Report - Listyono Putro, Jati Febriyanto Adi; Andy Nugroho; Septian Adi Permana; Andi Hermawan (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Tetanus, a severe neurologic disorder caused by Clostridium tetani neurotoxin, presents with progressive muscle rigidity and spasms. Grade III tetanus, characterized by generalized tetanus with severe spasms, carries a high mortality risk. Therapeutic plasma exchange (TPE) has emerged as an adjunctive therapy to remove circulating toxins and inflammatory mediators. Case presentation: We report a 50-year-old male with grade III tetanus following a minor injury. Despite standard treatment with tetanus immunoglobulin, antibiotics, and muscle relaxants, his condition deteriorated, necessitating intensive care unit (ICU) admission and mechanical ventilation. The patient underwent two sessions of TPE, demonstrating significant clinical improvement with reduced muscle spasms and successful ventilator weaning. Conclusion: This case highlights the potential benefit of TPE in managing severe tetanus, particularly in cases refractory to conventional therapy. Early recognition and aggressive management, including TPE, can improve outcomes in this life-threatening condition.